القيم التربوية المتضمنة في كتاب القراءة للصف السادس من التعليم الأساسي في الجمهورية العربية السورية - المطلق, فرح سليمان; زيد, نسرين علي (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدف البحث إلى: - تحليل كتاب القراءة المقرر في الصف السادس وفق معيار من تصميم الباحثة. - معرفة مدى تحقيق كتاب القراءة للقيم التربوية، ويتفرع عنه الهدف التالي: معرفة القيم العلمية- الروحية والأخلاقية-الاجتماعية -الإنسانية-الوطنية والقومية-الاقتصادية- الصحية والبيئية التي يتضمنها الكتاب، ونسبة تكرار كل منها. من أهم النتائج التي توصل البحث إليها أنّ نسبة تحقق مجالات القيم التربوية جاءت وفق التسلسل الآتي: في المرتبة الأولى مجال القيم الصحية والبيئية وكانت نسبته 26.04 %, وفي المرتبة الثانية مجال القيم العلمية بنسبة 16.33%, وفي المرتبة الثالثة مجال القيم الوطنية والقومية بنسبة بلغت 14.03%, وفي المرتبة الرابعة جاء مجال القيم الاجتماعية بنسبة أقل من سابقه بقليل بلغت 13.76%، وفي المرتبة الخامسة جاء مجال القيم الروحية والأخلاقية بنسبة 11.33%، وفي المرتبة السادسة جاء مجال القيم الاقتصادية بنسبة 9.71%، وفي المرتبة الأخيرة جاء مجال القيم الإنسانية بنسبة تحقق بلغت 8.08%. The research aims at analyzing the reading book scheduled in the sixth grade in accordance with the standard which the researcher intend to. It also aims at examining whether the reading book meets educational standards and this aim subsumes the knowledge of the scientific, spiritual, moral, social, humanitarian, national, and economic, health and environmental values which the book includes, and frequency proportion of each. One of the most important results of research is that the percentage of investigating the areas of educational values is sequenced as the following: The first field value is health and environmental which rated about 26.04%; the second field is scientific values which rated 16.33%; and the third is the national values and nationalism which rated 14.03%; the fourth is the social values which rated slightly less than its predecessors, in this case 13.76%; the fifth field in scale is the spiritual and moral values which rated 11.33%; the sixth is the economic values which rated 9.71%, and finally the field of human values which rated 8.08%.